2011
DOI: 10.5424/fs/20112003-11844
|View full text |Cite
|
Sign up to set email alerts
|

Soil dynamics and carbon stocks 10 years after restoration of degraded land using Atlantic Forest tree species

Abstract: Brazil's Atlantic Forest ecosystem has been greatly affected by land use changes, with only 11.26% of its original vegetation cover remaining. Currently, Atlantic Forest restoration is receiving increasing attention because of its potential for carbon sequestration and the important role of soil carbon in the global carbon balance. Soil organic matter is also essential for physical, chemical and biological components of soil fertility and forest sustainability. This study evaluated the potential for soil recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…The Ultisol site had taller trees than the Alfisol site (Table 2), a lower stem density, but higher wood volumes, although the basal areas were similar. Site conditions, such as higher natural fertility, higher clay content [30,31], and a higher water retention capacity [48,49] might initially have favored some individuals of species with a high competitive capacity, which dominated early in the process of stand development [50], suppressing the growth of other individuals. In contrast, in the Alfisol site, individuals might have grown up more evenly, since the soil conditions did not favor individual species with a higher competitive capacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ultisol site had taller trees than the Alfisol site (Table 2), a lower stem density, but higher wood volumes, although the basal areas were similar. Site conditions, such as higher natural fertility, higher clay content [30,31], and a higher water retention capacity [48,49] might initially have favored some individuals of species with a high competitive capacity, which dominated early in the process of stand development [50], suppressing the growth of other individuals. In contrast, in the Alfisol site, individuals might have grown up more evenly, since the soil conditions did not favor individual species with a higher competitive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration systems (experimental treatments), with different tree species compositions and arrangements, were as follows [31][32][33]…”
Section: Description Of the Restoration Systems Site Preparation Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that reference sites are crucial and essential in the restoration of ecosystems, driving both the evaluation of current conditions and the setting of management targets for specific points in the future (Harris & Diggelen, 2006;Pollock et al, 2012;). An increasing number of studies concerning biomass, carbon, nutrient dynamics and soil properties have indicated a significant disparity between restored forests and natural forests (Hughes et al, 1999;Rodrigues Nogueira Jr et al, 2011;Liao et al, 2012). We compared the measures of biodiversity and ecosystem functions between restored and reference forests.…”
Section: Taxonomic Groups Measured Functional Variables and Referencmentioning
confidence: 99%
“…Na região sudeste do Brasil, a maior parte das áreas a serem restauradas podem estar sob cobertura de pastagens ou abandonadas, e possuem diferentes potenciais de regeneração natural que podem ser aproveitados para a restauração passiva. As florestas secundárias decorrentes desse processo interferem nas propriedades do solo (PENUELA; DREW, 2004;, sendo observada tendência de diminuição da densidade aparente e aumento da porosidade RODRIGUES NOGUEIRA JR. et al, 2011), provavelmente devido a maior abertura de poros resultante do crescimento e morte das raízes (BEVEN; GERMANN, 2013). No entanto, medidas diretas dos processos que indicam o movimento da água no solo ainda são escassas e o tempo necessário para que o desenvolvimento da floresta seja percebido no condicionamento do solo é altamente variável.…”
Section: Introductionunclassified